Hydrometeorological Disasters Caused by Forgotten Local Wisdom (A Study of Local Wisdom ' Pilot' of the Gayo Community in Forest Conservation) - Linge, Abdiansyah (CV. Rayyan Dwi Bharata, 2026)
The hydrometeorological disaster in Aceh caused floods and landslides, causing numerous casualties and significant economic losses. The hydrometeorological disaster was exacerbated by the deterioration of forests in the highlands. Forest destruction is caused by many factors, one of which is the decline of local wisdom values related to forest exploitation.The norms and values of the Gayo highland community are closely linked to the interaction between nature and humans. Communities living alongside forests or in highland areas are the primary bulwark in maintaining forest sustainability. The community's role in forest preservation is to convey values or ideas that live within the community, referred to as local wisdom. This study focuses on the local wisdom of